Metonymy, metaphor, Patroklos, Achilles - Muellner, Leonard (Classica - Revista Brasileira de Estudos Clássicos, 2019)
This paper proposes an analysis of the relationship between tenor and vehicle in the simile that Achilles speaks to the weeping Patroklos at Iliad 16.5-11. Conceiving metaphor as based on resemblance (and, inevitably, difference) between tenor and vehicle and metonymy as based on attachment or connection between them, the simile is interpreted as a metaphor for the fused relationship between Achilles and Patroklos (the tenor) whose vehicle is the metonymic relationship between a mother fleeing both the catastrophic, violent consequences of war on women and at the same time her very own child who is desperately trying to stay connected to her mother by grasping at her clothing. The analysis invokes as a striking parallel the research of the pediatric psychoanalyst D. W. Winnicott on the birth of metaphor (in the form of a so-called transitional object) that results from the process of a child’s detachment at weaning from her mother.